Vehicle Monitoring with Web-Based Applications Utilizing High-Precision Positioning - Taufan Zandy Andrian; Uke Kurniawan Usman (Universitas Respati Yogyakarta, 2023)
Motorized vehicles have facilitated various human activities in everyday life. As technology develops, various features in driving have been added to the vehicle itself. Starting with the aim of adding comfort, even to increase the safety in the use of vehicles. In the current digital era, the vehicle monitoring process has been widely applied, especially in a number of smart vehicles that are integrated with a monitoring system from various vendors. A web-based application or commonly known as webapp, designed by PT. Telkom Indonesia, Tbk. named IndiCar, is an example of a monitoring system, which can be applied to vehicles that are commonly used daily. This is in line with the main goal of IndiCar, which is the digitalization of public vehicles, into smart vehicles. The implementation of monitoring using the IndiCar webapp can make it easier for vehicle users, both in personal and institutional use, to track and diagnose a vehicle, regarding a number of factors such as precise location, track traveled, to the condition of various vehicle components, utilizing a number of sensors applied to the IndiCar system.